Influence of obesity on soluble endoglin and transforming growth factor β1 in women with polycystic ovary syndrome - Nearmeen M. Rashad; Abdelaziz I. Amin; Ayman E. Ali; Manar H. Soliman (Middle East Fertility Society Journal, 2018)
Background: Chronic low-grade inflammation is a common feature of obesity and polycystic ovary syndrome (PCOS). There is dysregulation of transforming growth factor (TGF)-β1 in women with PCOS, soluble endoglin (sEng) is a non-signaling coreceptor of the TGF-β modulating its responses. We aimed for the first time to investigate the impact of obesity on sEng and TGF-β1 in women with PCOS. Methods: Case control study enrolled seventy patients diagnosed with PCOS and50 control group. High sensitivity C-reactive protein (hs-CRP) and sEng levels were assessed using an enzyme-linked immunosorbent assay (ELISA). Results: Our results revealed that, PCOS patients had higher values of TGF-β1 and lower levels of sEng. Among both control and PCOS patients, obese subjects had higher values of TGF-β1 and lower levels of sEng. Receiver operating characteristic curve (ROC) analysis revealed that, the power of sEng was more sensitive and specific than TGF-β1 in diagnosis of PCOS and in differentiating obese from lean group. Nonetheless, the diagnostic power of both TGF-β1 and sEng was highly significant. Conclusion: Obese subjects of control and PCOS groups had higher values of TGF-β1 and lower values of plasma sEng level than lean subjects, the diagnostic power of both TGF-β1 and sEng was highly significant thus, sEng and TGF-β1 could be a useful diagnostic biomarker of PCOS. Keywords: Obesity, PCOS, TGF-β1, Soluble endoglin